Perkembangan Thariqah Naqsyabandiyah terhadap Masyarakat Maro Sebo Ulu: Desa Sungai Ruan Ilir dalam Perspektif Peran Sosialnya - Abd. Manap; Ahmad Syukri; Mohd. Arifullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The history of the development of Tariqah an Naqsyabandiyah began in the 14th century in Türkiye from Shaykh Muhammad bin Muhammad Baha'uddin an Naqshbandi. Tariqah developed rapidly in Maro Sebo Ulu District in 2015-2020, previously centered in Sungai Ruan Ilir Village in 2007/2008. Thariqah Naqsyabandiyah in Maro Sebo Ulu is a pure Islamic teaching that focuses on Sufism preached by Imam Syafi'i (Young Sheikh Muhammad Khairun Nasihin). The beginning of Tariqah Naqsyabandiyah was present in Jambi Province when it was brought by Muhammad 'Ali Idrus (Teacher Bambang). The social role that Tariqah Naqsyabandiyah brings to society contains a lot of goodness, being social, minimizing polytheism and crime in the local environment and others. And da'wah invites people to accept the guidance of Allah SWT. Previously, their work was full of evil and neglect, after being gently taught the ways of Rasulullah SAW, they wanted to repent and take this holy path, namely Tariqah an Naqshbandiyah. The research method used is a qualitative research method. This research method is research that produces descriptive data in the form of words or spoken or written in the form of interviews, scientific works and others. The conclusion is that Tariqah Naqsyabandiyah is an Islamic teaching from Rasulullah SAW and was developed by Muhammad Baha'uddin An Naqsyabandi over time until it reached Jambi by Muhammad Ali Idrus and arrived in Maro Sebo Ulu District brought by the Young Sheikh Muhammad Khairun Nasihin until he succeeded in preaching it despite various obstacles such as opinions and criticism from the public who do not believe in his presence.